Effect of Lidocaine on Viability and Gene Expression of Human Adipose–derived Mesenchymal Stem Cells: An in vitro Study. Issue 11 (30th May 2019) - Nie, Hai; Kubrova, Eva; Wu, Tao; Denbeigh, Janet M.; Hunt, Christine; Dietz, Allan B.; Smith, Jay; Qu, Wenchun; van Wijnen, Andre J.
Abstract : Objective: To assess the biologic effects of lidocaine on the viability, proliferation, and function of human adipose tissue–derived mesenchymal stromal/stem cells (MSCs) in vitro. Methods: Adipose‐derived MSCs from three donors were exposed to lidocaine at various dilutions (2 mg/mL to 8 mg/mL) and exposure times (0.5 to 4 hours). Cell number and viability, mitochondrial activity, and real‐time reverse‐transcriptase quantitative polymerase chain reaction (RT‐qPCR) were analyzed at 0 (immediate effects) or 24 and 48 hours (recovery effects) after treatment with lidocaine. Results: Trypan blue staining showed that increasing concentrations of lidocaine decreased the number of observable viable cells. 3‐[4, 5, dimethylthiazol‐2‐yl]‐5‐[3‐carboxymethoxy‐phenyl]‐2‐[4‐sulfophenyl]‐2H‐tetrazolium (MTS) assays revealed a concentration‐ and time‐ dependent decline of mitochondrial activity and proliferative ability. Gene expression analysis by RT‐qPCR revealed that adipose‐derived MSCs exposed to lidocaine express robust levels of stress response/cytoprotective genes. However, higher concentrations of lidocaine caused a significant downregulation of these genes. No significant differences were observed in expression of extracellular matrix (ECM) markers COL1A1 and DCN except for COL3A1 ( P < .05). Levels of messenger RNA (mRNA) for proliferation markers (CCNB2, HIST2H4A, P < .001) and MKI67 ( P < .001) increased at 24 and 48 hours. Expression levels of several transcription factors— including SP1, PRRX1, and ATF1—were modulated in the same manner. MSC surface markers CD44 and CD105 demonstrated decreased expression immediately after treatment, but at 24 and 48 hours postexposure, the MSC markers showed no significant difference among groups. Conclusion: Lidocaine is toxic to MSCs in a dose‐ and time‐ dependent manner. MSC exposure to high (4‐8 mg/mL) concentrations of lidocaine for prolonged periods can affect their biologic functions. Although the exposure time in vivo is short, it is essential to choose safe concentrations when applying lidocaine along with MSCs to avoid compromising the viability and potency of the stem cell therapy.